Parental influence on children's answers to an oral-health-related quality of life questionnaire - Ana Flávia GRANVILLE-GARCIA; Monalisa Cesarino GOMES; Laíza Rocha DANTAS; Lívia Rocha DANTAS; Bruno Rafael Cruz da SILVA; Matheus de França PERAZZO; Maria Betânia Lins Dantas SIQUEIRA (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of the study was to evaluate parental influence on children's answers to an oral health-related quality of life (OHRQoL) questionnaire. A cross-sectional study was conducted with a non-probabilistic sample of 84 pairs of 5-year-olds and parents/guardians. The participants were selected from a primary family healthcare center in Campina Grande, Brazil. First, the children and parents answered respective versions of the Scale of Oral Health Outcomes for Five-Year-Old Children (SOHO-5). Seven days later, the children answered their version of the SOHO-5, without the presence of their parents/guardians, and underwent a clinical exam of dental caries, traumatic dental injury and malocclusion, by a previously calibrated researcher. Statistical analysis involved a comparison of mean scores and the calculation of the intraclass correlation coefficient (ICC). Poisson regression models were used to associate the variables (α = 5%). No significant differences were found between the mean SOHO-5 scores of the children when alone or accompanied by parents/guardians (p > 0.05). The ICC between the answers of the children alone or accompanied was 0.84. White spot (PR = 6.32; 95%CI: 1.36 - 29.40) and cavitated lesions (PR = 9.81; 95%CI: 3.22 - 29.85) had an impact on OHRQoL, according to the children's self-report, whereas cavitated lesions (PR = 90.52; 95%CI: 13.26 - 617.74) and anterior open bite (PR = 1.95; 95%IC: 1.07 - 3.53) remained on the final model, according to the parents' version of the SOHO-5. In conclusion, parents did not influence the children's responses, and dental caries are the oral health problem exerting the greatest impact on the children's OHRQoL.